Importing, exporting and productivity in Irish manufacturing - Fergal McCann (University College Dublin, UCD School of Economics, 2009)
The impact of international trade on firm productivity is tested by accounting for firms' import as well as export status for a large panel of Irish manufacturing firms. Two-way traders and exporters-only are found to be the most productive firms, with a significant gap between them and importersonly and non-traders. tfp is calculated using a modified version of the Olley and Pakes (1996) estimator, taking account of a four-category trade status. Selection of the most productive firms into exporting or importing is not found in any robust sense. Fixed effcts, as well as Propensity Score Matching with Difference in Differences, are used to calculate productivity improvements from entering into international trade. These improvements are found to be highly contingent on export status, with import status being unimportant. The key finding of the paper is that the gains from trade, for Ireland at least, appear to lie on the export side. Interestingly, quitting trade leads to a mirror image effect to that of entry for all trade statuses.
hdl:10197/2620
Keywords: F10; F14; L25; 330; Trade orientation; heterogeneous firms; Productivity